Advances in 3D bioprinting for modeling the blood-brain barrier in neurodegenerative diseases - Tan, Shirleen; Qiu, Lifeng; Lee, Jolene Wei Ling; Zeng, Li (Frontiers in Molecular Biosciences, 2025)
The growing burden of neurodegenerative diseases (NDD) on healthcare systems, driven by global aging population, has increased interest in modelling the blood-brain barrier (BBB). While microfluidic platforms have been widely used to model the BBB, they remain limited by complex fabrication techniques, low-throughput, and restricted control over BBB geometry. Recent advancements in three-dimensional (3D) bioprinting offer promising strategies to overcome these constraints and to enable the generation of physiologically relevant BBB models. This review examines the recent progress in 3D bioprinting approaches to model human in vitro BBB, with a focus on their applications in NDD research. We first summarise current 3D bioprinting techniques and strategies, including the selection of bioinks and geometry design. Subsequently, we address the evaluation methods for in vitro BBB modelling and their relevance to disease modelling. Finally, we identify key challenges and future directions aimed at improving resolution, reproducibility, and functional 3D-printed BBB constructs for use in NDD modelling and drug development.